Swearing as a Response to Pain: Assessing Hypoalgesic Effects of Novel “Swear” Words - Stephens, Richard; Robertson, Olly (Frontiers in Psychology, 2020)
Previous research showing swearing alleviates pain is extended by addressing emotion arousal and distraction as possible mechanisms. We assessed the effects of a conventional swear word (“fuck”) and two new “swear” words identified as emotion arousing and distracting: “fouch” and “twizpipe”. A mixed sex group of participants (N = 92) completed a repeated measures experimental design augmented by mediation analysis. The independent variable was repeating one of four different words: “fuck” v. “fouch” v. “twizpipe” v. a neutral word. The dependent variables were emotion rating, humour rating, distraction rating, cold pressor pain threshold, cold pressor pain tolerance, pain perception score and change from resting heart rate. Mediation analyses were conducted for emotion, humour and distraction ratings. For conventional swearing (“fuck”), confirmatory analyses found a 32% increase in pain threshold and a 33% increase in pain tolerance, accompanied by increased ratings for emotion, humour and distraction, relative to the neutral word condition. The new “swear” words, “fouch” and “twizpipe” were rated as more emotional and humourous than the neutral word but did not affect pain threshold or tolerance. Changes in heart rate and pain perception were absent. Our data replicate previous findings that repeating a swear word at a steady pace and volume benefits pain tolerance, extending this finding to pain threshold. Mediation analyses did not identify a pathway via which such effects manifest, although distraction appears to be of little importance while emotion arousal appears worthy of future study.